Economic sentiment indicator as a demand determinant - Altin, M.; Uysal, Muzaffer (Croatian National Tourist Board, 2014)
© 2014 Cognizant Comm. Corp.This study incorporates the concept of economic sentiment indicator (ESI) into demand studies along with more traditional variables such as interest rate, relative price, and exchange rate. The study utilizes ARIMA and ARDL bound test approach to cointegration using 15 EU member countries to Turkey. The study supports that ESI is a good indicator to gauge and monitor tourism demand, and adding tourists' state of mind into the demand equation could reduce errors and increase variance in explaining tourist arrivals. Policy makers should monitor ESI as it fluctuates over time and assess its potential effect on visitation behavior. Using this information generated from the study, government officials and tourism suppliers could adjust their promotional activities and expenditures.